Escape from Red China - Loh, Robert, 1924-; Evans, Humphrey (New York: Coward-McCann, 1962)
The experiences and attitudes of a man who lived under Chinese Commu nism, rising to a position of importance before his decision to flee to the West, whose story describes much of life and society under Maoism.
Keywords: Communism -- China; China -- Social conditions -- 1949-1976.; China -- Social conditions